Tujuan Penciptaan Manusia Dalam Kajian Al-Quran - Shofiyah, Nida; Sumedi, Sumedi; Hidayat, Tatang; Istianah, Istianah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
The purpose of this study is to analyze the purpose of human creation in the study of the Quran. This research uses qualitative approach and literature review method. Based on the results of the discussion, humans are seen as a